Nurses' perceptions of providing psychosexual care for women experiencing gynaecological cancer - Williams, Natalie; Hauck, Yvonne; Bosco, Anna (xxx, 2017)
Purpose To gain insight into how Western Australian nurses conceptualise the provision of psychosexual care for women undergoing gynaecological cancer treatment and how this aligns with nurses globally. Methods A qualitative descriptive design was chosen to facilitate insight into nurses' perspectives of their reality. Seventeen nurses working at a tertiary women's hospital in Western Australia participated in one-on-one interviews and were asked to describe their perceptions and identify factors that facilitate or challenge psychosexual care provision. Results Data analysis revealed five themes affecting the provision of psychosexual care: (1) Nurses use strategies to aid the conversation (subthemes: supporting the woman, facilitating engagement); (2) Women have unique psychosexual needs (subthemes: diversity, receptiveness); (3) Nurses are influenced by personal and professional experience and values (subthemes: confidence, values, making assumptions); (4) Systems within the health service affect care (subthemes: being supported by the system, working as a team); and (5) Society influences attitudes around sexuality. Nurses' views differed around whether these factors had a positive or negative impact on the conversation required to provide this care. Conclusions Factors influencing nurses' provision of psychosexual care are multifaceted and differ amongst nurses. Recommended strategies to improve service provision include guidelines and documentation to integrate assessment of psychosexual issues as standard care, encouraging shared responsibility of psychosexual care amongst the multidisciplinary team and implementing education programs focussed on improving nurses' confidence and communication skills.